Impact of COVID-19 outbreak on the blood donation and utilization and strategies adopted to combat it in a tertiary care center of Jammu province - Dutt, Neeti; Sharma, Sushil; Sidhu, Meena (International Journal of Research in Medical Sciences, 2022)
Background: The COVID-19 pandemic has major implications for blood transfusion. There are uncertain patterns of demand, and transfusion institutions need to plan for reductions in donations and loss of crucial staff because of sickness and public health restrictions. A range of strategies need to be planned to maintain ongoing equitable access to blood for transfusion during the pandemic, in addition to providing new therapies such as convalescent plasma. The main role of transfusion institutions during this period, is the monitoring of supply and demand so that sufficient blood stocks are maintained to support ongoing critical needs. The main aim of our study was to study the impact of COVID-19 outbreak on blood transfusion services (BTS) and to identify the challenges faced by our blood center and mitigation strategies adopted to combat it. Methods: Total number of donations and total number of blood and its components issued were noted from the donor and issue registers respectively, both during the pre-COVID and COVID-19 pandemic and the results were compared thereafter. Various strategies were adopted during the COVID pandemic in order to maintain balance between demand and supply of blood and its products. Results: There has been sudden decrease in the number of blood donations in the month of April 2020 (35%) in the COVID pandemic as compared to pre-COVID time with percentage difference of 65%. This was followed by gradual decrease in the no. of donations in COVID pandemic when compared with donations in the pre-COVID time. The percentage difference in blood donation gradually improved over a period of time from 65% in April 2020 to 7% in April 2021. Similarly, no. of blood units issued also decreased from 1147 in April 2019 to 553 units in April 2020. Conclusions: The BTS need to provide an uninterrupted blood supply, and this stays true even in the face of a pandemic. The plan of action has to be started early so that the supply can be maintained and monitored effectively. Health-care workers being one of the main pillars in the fight against COVID-19 have to be supported and protected.